Health through the eyes of youths: a qualitative study - Nikki Ow; Rebecca Zivanovic; Karen Tee; Steve Mathias; Steve Mathias; Skye Pamela Barbic; Skye Pamela Barbic; Skye Pamela Barbic (Frontiers Media S.A., 2024)
BackgroundEmerging definitions of health have suggested a shift in focus to one's ability to manage their health condition, function, and social determinants of health. The construct of health for youths with mental health and substance use disorders (MHSU) is complex and multi-dimensional with interplay between biological, behavioral, and social conditions. Expanding definitions of health is crucial in the measurement of health and evaluation of integrated youth services (IYS) systems for people with MHSU disorders. Hence, it is critical to understand the construct of health from the perspective of a young person living with a MHSU disorder.MethodsThis study was conducted using inductive thematic analysis. Three focus groups were conducted from July to August 2017.ResultsA total of 22 youths (17-24 years) took part in this study. Results showed that health is a multidimensional construct situated in the ecosystem of a person's environment. Health can be understood from two macro themes: Individual health and Determinants of health. It consisted of physical health, mental health, day-to-day functioning, and being in control of your own health condition. Systemic and social factors were factors that influenced the state of health.ConclusionThis study contributes to a conceptualization of good health in youth with MHSU disorders. This conceptualization can aid in the development of more accurate measures of health and functioning and the evaluation of mental health services for youth with MHSU.